SAP Cloud Migration: Strategies, Challenges, and Best Practices - Srinivas Reddy Pinnapureddy, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive technical article explores the strategies, challenges, and best practices for successful SAP cloud migration in today's rapidly evolving digital landscape. It examines various aspects of cloud migration, including market trends, implementation approaches, and critical success factors. The article provides detailed insights into three primary migration strategies: Greenfield, Brownfield, and Bluefield, along with their respective technical considerations and use cases. It covers cloud platform selection criteria, focusing on major providers like AWS, Azure, and GCP, while discussing their specific capabilities and differentiating features. The article delves into essential aspects of migration planning, including infrastructure requirements, data security, system integration, and performance optimization. Special attention is given to zero downtime migration techniques, outlining pre-migration assessment, execution strategies, and post-migration optimization procedures. The article emphasizes the importance of proper planning, technical preparation, and continuous monitoring throughout the migration journey.
Keywords: SAP Cloud Migration; Zero Downtime Implementation; Enterprise Architecture; Digital Transformation; Cloud Platform Selection